Immunomodulatory effect of structurally-characterized mushroom sclerotial polysaccharides isolated from Polyporus rhinocerus on human monoctyes THP-1. (February 2018) - Liu, Chaoran; Choi, Man Wing; Li, Xiaojie; Cheung, Peter C.K.
Highlights: PRW and mPRSon were isolated from the sclerotia of Polyporus rhinocerus . PRW and mPRSon were heteroglycan-protein complex and beta-glucan, respectively. PRW could bind to the complement receptor 3 and induce maturation of THP-1 cells. mPRSon could bind to Dectin-1 but could not activate the Dectin-1 signaling in THP-1. PRW is more immunopotent than mPRSon. Abstract: Two high molecular weight (MW larger than 788 kDa) mushroom polysaccharides extracted by hot water (PRW) and micronized sonication-assisted cold alkali (mPRSon), were isolated from the sclerotia of Polyporus rhinocerus . PRW was a polysaccharide-protein complex with a highly branched (degree of branching DB 0.60) β-D-mannoglucan while mPRSon was a hyper-branched β-glucan (DB 0.85). PRW could bind to complement receptor 3 (CR3) and significantly induced THP-1 differentiation evidenced by cell morphology and enhanced phagocytic activity. A significant increase in the expression of surface markers including CD14, CD11b and HLA-DR as well as enhanced production of cytokines including IL-8, RANTES, GRO, MCP-1, MCP-2 and IL-6 were observed on THP-1 cells treated with PRW. In contrast, mPRSon could not either activate the Dectin-1 signaling or induce the THP-1 differentiation. High MW and DB mushroom sclerotial polysaccharide which has a structure of heteroglycan and protein is more immunopotent than pure homoglycan.